The maturation state and density of human cartilage microtissues influence their fusion and development into scaled-up grafts - Kelly, Daniel (My University, 2025)
Functional cartilaginous tissues can potentially be engineered by bringing together numerous microtissues (μTs) and allowing them to fuse and re-organize into larger, structurally organized grafts. The maturation level of individual microtissues is known to influence their capacity to fuse, however its impact on the long-term development of the resulting tissue remains unclear. The first objective of this study was to investigate the in- fluence of the maturation state of human bone-marrow mesenchymal stem/stromal cells (hBM-MSCSs) derived microtissues on their fusion capacity and the phenotype of the final engineered tissue. Less mature (day 2) cartilage microtissues were found to fuse faster, supporting the development of a matrix that was richer in sulphated glycosaminoglycans (sGAG) and collagen, while low in calcium deposits. This enhanced fusion in less mature microtissues correlated with enhanced expression of N-cadherin, followed by a progressive increase in markers associated with cell-extracellular matrix (ECM) interactions. We then engineered larger constructs with varying initial numbers (50, 150 or 300 μTs per well) of less mature microtissues, observing enhanced sGAG synthesis with increased microtissue density. We finally sought to engineer a scaled-up cartilage graft by fusing 4,000 microtissues and maintaining the resulting constructs under either dynamic or static culture conditions. Robust and reliable fusion was observed between microtissues at this scale, with no clear benefit of dynamic culture on the levels of matrix accumulation or the tensile modulus of the resulting construct. These results support the use of BM-MSCs derived microtissues for the development of large-scale, engineered functional cartilaginous grafts. Statement of significance: Microtissues are gaining attention for their use as biological building blocks in the field of tissue engineering. The fusion of multiple microtissues is crucial for achieving a cohesive engineered tissue of scale, however the impact of their maturation level on the long-term properties of the engineered graft is poorly understood. This paper emphasizes the importance of using less mature cartilage microtissues for supporting appropriate cell-cell interactions and robust chondrogenesis in vitro. We demonstrate that tissue development is not negatively impacted by increasing the initial numbers of microtissues within the graft. This biofabrication strategy has significant translation potential, as it enables the engineering of scaled-up cartilage grafts of clini- cally relevant sizes using bone marrow derived MSCs
Keywords: cartilaginous tissues; microtissues (μTs); human bone-marrow mesenchymal stem/stromal cells (hBM-MSCSs); cartilaginous tissues; microtissues (μTs); human bone-marrow mesenchymal stem/stromal cells (hBM-MSCSs)